European english varieties: a contribution to the study of the characteristics of nativisation processes - Monteiro, Maria Goreti da Silva (2012)
Margie Berns (6-7) states that as a result of the fact that European English is used by a rising number of non-native speakers, their English is becoming more and more distinct from the native speakers’ variety. Because this is the language mostly used in European Union institutions and is, simultaneously, the language traditionally used for doing business, Continental Europeans are continuously bending British English so as to convey the full significance of their own language. Consequently, Europeans are communicating in a growing number of European English varieties. As such, the purpose of this paper is to study a corpus of business correspondence, which took place in English as a foreign language among technicians from seven different European countries, in order to find individual features in terms of grammar, word order and vocabulary and thus contribute to establish the characteristics of different European varieties of English.